Peer feedback : quality and quantity in large groups - Hattum-Janssen, Natascha van (2012)
Providing peer feedback is an activity that does not only support the receiver of the feedback in his or her learning process, it is also useful for those who provide feedback, as they have to critically analyse the work or performance of colleagues [1]. Apart from the specific contents of peer feedback comments, the quantity and the diversity of peer feedback in comparison with the quantity and diversity of teacher feedback is one of the main advantages on the inclusion of peer feedback in the assessment methods of a course. This article describes the second edition of a 15-ECTS project-oriented course for Informatics Engineering Master’s students at the University of Minho, in which peer assessment of team performance is part of the assessment method. In the first year in which the peer assessment method was implemented, students worked in large teams and assessed their peers at four moments on the behaviour in the team, using a single comment to justify all grades given on the assessment criteria. In the second edition, students used a comment for each one of the assessment criteria, multiplying as such the quantity and diversity of the comments. This article seeks to explore the change of quality of peer feedback for the second edition in order to improve the current model of peer feedback used in this and other engineering courses and make peer feedback as helpful as possible for both the giving as well as the receiving students.